The historical variability of the age-crime relationship - Greenberg, David F. (Journal of quantitative criminology, 1994)
Methodological problems arising in fitting nonlinear regressions to a dataset are identified in context of research on the age-crime relationship. A modified chisquare distribution is fit to the age distribution of the seven Index crimes for the years 1952, 1957, 1962, 1967, 1972, 1977, 1982, and 1988 to assess the historical invariance of the distribution. Problematic features of Britt's ( J. Quant. Criminol. 8, 175–187, 1992) analysis of the same data are highlighted.